Adoption of Gender - Specific Innovations by Women in Gombe State - A C Anyanwu; A E Agwu; A P Musa (Journal of Agricultural Extension, 2015)
The main purpose of this study was to determine the level of adoption of selected gender - specific innovations in Gombe State. A structured interview schedule, administered to 89 women in 10 randomly selected blocks in the state, was the major instrument used collection. for data The data were analysed using means and percentages. Results of the study show that there is generally a low level of adoption for most of the innovations except processing and utilisation of soybeans and processing and utilisation of vegetables. Also, most women are not aware of the improved local stove and groundnut oil extractor. The results also reveal that clients are receptive to extension agents and hence, view them as the major source of information influencing the adoption of gender- specific innovations. Adoption of the innovations is influenced by varied factors, the major being the ease of use of the innovations. Also, cost of use and lack of funds are the major problems associated with the adoption of the innovations. It is therefore recommended that innovations with low levels of adoption be reintroduced and efforts intensified to raise the level of adoption by alleviating most of the problems inhibiting adoption and the use of appropriate methods of communication such as demonstrations so as to achieve high level of adoption.